The novel M4 PAM PET tracer [11C] MK‐6884: a novel biomarker for measuring target engagement of muscarinic M4 positive allosteric modulators (PAMs) as well as cholinergic tone in patients with Alzheimer’s disease - Li, Wenping; Basile, Anthony S; Tong, Ling; Van Laere, Koen; Masdeu, Joseph C.; Hostetler, Eric D; Marshall, Fiona; Uslaner, Jason M. (Alzheimer's & dementia, 2022)
Background The muscarinic acetylcholine receptor 4 (M4) has attracted attention as a target for treating neuropsychiatric symptoms, such as agitation and aggression, associated with Alzheimer’s disease. We have developed novel selective, potent, and in vivo suitable M4 positive allosteric modulators (PAMs) and demonstrated robust pharmacology in preclinical models predictive of antipsychotic and pro‐cognitive effects. Importantly, we have also shown that these selective M4 PAMs produce greater therapeutic margins for cholinergic adverse effects compared to less selective muscarinic receptor agonists. Methods To enable translation in the clinic, we set out to discover an M4 PAM PET tracer suitable for measuring central receptor occupancy (RO). Result [11C]MK‐6884 binds with high affinity and selectivity to the allosteric site on the M4 receptor that our other M4 PAMs bind. The affinity of [11C]MK‐6884 was found to be influenced by the concentration of orthosteric agonist in vitro and in vivo, consistent with the high cooperativity of the molecule in vitro. PET studies successfully determined the target engagement of PAMs to enable modeling the relationship between drug plasma exposure, RO, and pharmacodynamic activity. Donepezil increased the tracer binding potential of [11C]MK‐6884 in rhesus and healthy human subjects, confirming in vivo the influence of cholinergic tone on [11C]MK‐6884 binding that was observed in vitro. Consistent with a presumed cortical deficit in synaptic acetylcholine, [11C]MK‐6884 PET studies in AD patients showed lower cortical binding potential compared to healthy elderly participants, as well as notable cortical heterogeneity and bilateral asymmetry of M4 receptor binding in AD patients. Striatal binding potential was unchanged in these different populations. Conclusion Our findings demonstrate that the M4 PAM PET tracer [11C]MK‐6884 is a useful tool for determining target engagement of M4 PAMs, as well serving as a unique probe to study changes in cholinergic neurotransmission in neurodegenerative disease. The Enigma Biomedical Group has an exclusive license agreement with Merck & Co., Inc., for the global development and commercialization of MK‐6884. This allows Enigma and its partner, Cerveau Technologies Inc. to provide biomarkers to industry and academia to accelerate research in the field of neurodegenerative and neuropsychiatric diseases.